2022
DOI: 10.1093/ije/dyac235
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work and risk of aggressive prostate cancer in the Norwegian Offshore Petroleum Workers (NOPW) cohort

Abstract: Background Night shift work may acutely disrupt the circadian rhythm, with possible carcinogenic effects. Prostate cancer has few established risk factors though night shift work, a probable human carcinogen, may increase the risk. We aimed to study the association between night shift work and chlorinated degreasing agents (CDAs) as possible endocrine disrupters in relation to aggressive prostate cancer as verified malignancies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“… 16 Another study reported that the risk of aggressive prostate cancer was significantly increased in the group with more than 19.5 years of rotating shifts (HR: 1.86; 95% CI: 1.18–2.91). 38 2) Consistency: Increased risk of prostate cancer in night-shift workers has been consistently observed in several epidemiological studies of various population and work schedules. 16 28 29 30 31 32 3) Temporality: The 2 workers were diagnosed with prostate cancer after doing night shift work for 17 and 35 years, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“… 16 Another study reported that the risk of aggressive prostate cancer was significantly increased in the group with more than 19.5 years of rotating shifts (HR: 1.86; 95% CI: 1.18–2.91). 38 2) Consistency: Increased risk of prostate cancer in night-shift workers has been consistently observed in several epidemiological studies of various population and work schedules. 16 28 29 30 31 32 3) Temporality: The 2 workers were diagnosed with prostate cancer after doing night shift work for 17 and 35 years, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…4) Biological gradient: Exposure-response curves using non-linear model showed a linear increase in risk of aggressive prostate cancer with 18–26 years of rollover shifts. 38 5) Plausibility: The biological mechanism was provided by the results of studies confirming the effects of light and dark schedule changes on immunosuppression, chronic inflammation, and cell proliferation 23 24 25 and also increased risk of cancer incidence was reported in animal studies. 20 6) Coherence: This epidemiological association between night-shift work and prostate cancer does not contradict natural history and biology of prostate cancer.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For outcome classification, most studies used all prostate cancer cases regardless of their stage. However, three cohort reports (from two cohort studies) used only aggressive stages [ 28 , 37 ]. In addition, one cohort study used mortality due to prostate cancer as the outcome instead of the incidence [ 38 ].…”
Section: Discussionmentioning
confidence: 99%